Non-lysosomal protein degrading systems in chicken skeletal muscle - Arnold, Jane Elizabeth (Division of Medical Biochemistry and Structural Biology, 2017)
In an attempt to understand the roles played by the ubiquitin-dependent and calpain pathways in protein degradation in chicken skeletal muscles, biochemical studies were conducted on components of these two systems as well as their potential endogenous and exogenous substrates. ATP- and ubiquitin-dependent breakdown of endogenous proteins (measured by tyrosine release) or exogenous proteins (measured by the appearance of trichloroacetic acid-soluble radiolabel after incubation with 125I-lysozyme) took place in muscle extracts; the specific activities of these processes were significantly lower than those detected in rabbit reticulocytes. Conjugation of ubiquitin to a subset of endogenous proteins was detected by incubating muscle extracts (fraction II: depleted of ubiquitin by DEAE-cellulose chromatography) with 125I-ubiquitin and Mg2+-ATP, followed by analysis of the radiolabelled conjugates by one-dimensional polyacrylamide gel electrophoresis in the presence of SOS, and autoradiography. Discrete conjugates were formed with apparent molecular weights between 30 -100 000, as well as a large number of undifferentiated entities of higher molecular weights. Conjugation of ubiquitin to the exogenous protein lysozyme was detected only when fresh, as opposed to previously frozen fraction II preparations were assayed: three bands were obtained, as opposed to the six ubiquitin conjugates formed by reticulocyte extracts. The muscle system catalyzed the ubiquitination of partially purified myofibrillar proteins, principally myosin and possibly actin. Fractionation of the ubiquitin-activating enzymes into El and E2 on the one hand, and E3 on the other, permitted mixing experiments to be conducted by means of conjugation assays, and confirmed the low content of E3 in muscle as opposed to reticulocytes. Fraction II from muscle displayed ubiquitin conjugate-degrading activity but again this was less active than in reticulocytes. A number of other proteolytic activities, independent of ubiquitin, were also present. Isopeptidases, active on 125I-ubiquitin conjugates were strongly inhibited by sulphydryl alkylating agents such as N-ethylmaleimide. The overall picture of the ubiquitin pathway in muscle is one where many proteins may be converted into long-lived conjugates but not in all cases requiring the action of E3: some E3-dependent protein degradation undoubtably does occur in this physiologically basal system. Formation of a ubiquitin conjugate of the ubiquitinactivating enzyme (E1) and some of the ubiquitin carrier proteins (E2 's) was detected during incubations of 125Iubiquitin and ATP lasting 2 hr or longer. Because treatment of such systems with NaOH, even at early times during the incubations, greatly enhanced the appearance of the same entities, the phenomenon appeared to be one of auto-, rather than E3-mediated ubiquitination. The bonds involved had properties compatible with their being peptidic in nature, and their formation occurred from ubiquitin thiolesters bound to E1 and E2. The protease inhibitor and alkylating agent, TLCK, when pre-incubated with fraction II for 2 hr before the addition of 125I-ubiquitin and ATP, greatly enhanced the subsequent auto-ubiquitination of E1 in the absence of NaOH treatment, and caused the inhibition of its adenylate-forming and thiolester-transferring activities: thus ubiquitin transfer to E2's and further to other acceptors was markedly impaired. such an inactivation of El by TLCK may, in a manner analogous to that described in the thermolabile ts85 mutants (Finley et al., 1984), be the basis of the action of this agent to block the cell cycle in late G2 or early M phase (Schnebli & Haemmerli, 1974). TLCK-induced inactivating auto-ubiquitination of El may be an important tool for the study of ubiquit-independent processes which (apart from possible intrinsic protease activity), all appear to require the activity of this enzyme. The number of calpain species existing in chicken skeletal muscle is controversial with only one (Ishiura et al., 1978) or three (Wolfe et al., 1985) species having been reported. When extracts of chicken skeletal muscle were applied to a DEAE-cellulose column and the bound protein eluted in a linear salt gradient, two calpain activities, separated from their endogenous inhibitors (calpastatins), were detected. The first eluting activity, "calpain I", was active at low ca2+ concentrations, was heat-labile and had a lower apparent molecular weight on gel filtration when compared with the later eluting activity which appeared to be a typical calpain II species. "Calpain I". was not an autolytic product of calpain II but appeared to be derived from a more heat-stable calpain I species. A proportion (up to 14%) of the calpains in crude muscle extracts was bound to membrane fractions in the presence of ca2+; this could be removed by EGTA treatment. In addition, membrane-bound fractions examined by 9el filtration contained calpain· forms of an apparent molecular · weight lower than that of calpain which had not been membrane-associated. Membrane binding of the calpains (especially of calpain II), may be important in physiological activation.